WORKPLACE CHALLENGES AND OPPORTUNITIES: LEADING OUTSIDE THE BOX. Issue 83 (January 2017) - Taulbert, Clifton L.
Abstract : Thinking outside the box has become such a familiar term that it has lost much of its meaning and power. Taulbert aims to reclaim some of the magic based on his own work as an entrepreneur breaking out of the segregated South, and related experience. "To embrace outside‐the‐box leadership, " he writes, "is to allow your imagination to fuel your creativity, which most often takes us beyond the known and familiar to the world of possibilities—the winning lane in today's marketplace." This requires distancing from the past, and facing fears (such as of the unknown and of failure), envy, and lack of ambition—things few leaders would want to admit about themselves.